DLP 4D printing of multi-responsive bilayered structures - Mainik, Philipp; Hsu, Li-Yun; Zimmer, Claudius W.; Fauser, Dominik; Steeb, Holger; Blasco, Eva (Advanced Materials Technologies, 2023)
Advances in soft robotics strongly rely on the development and manufacturing of new responsive soft materials. In particular, light-based 3D printing techniques, and especially, digital light processing (DLP), offer a versatile platform for the fast manufacturing of complex 3D/4D structures with a high spatial resolution. In this work, DLP all-printed bilayered structures exhibiting reversible and multi-responsive behavior are presented for the first time. For this purpose, liquid crystal elastomers (LCEs) are used as active layers and combined with a printable non-responsive elastomer acting as a passive layer. Furthermore, selective light response is incorporated by embedding various organic dyes absorbing light at different regimes in the active layers. An in-depth characterization of the single materials and printed bilayers demonstrates a reversible and selective response. Last, the versatility of the approach is shown by DLP printing a bilayered complex 3D structure consisting of four different materials (a passive and three different LCE active materials), which exhibit different actuation patterns when irradiated with different wavelengths of light.